(untitled) (Sustainability in Debate, 2015)
Elizabeth Kolbert. The Sixth Extinction: an unnatural history. New York: Henry Holt and Company, 2014. Notas, bibliografia, fotografia, índice remissivo. 319p. ISBN 978-0805092998.